2015
DOI: 10.1007/s40089-014-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of silver nanoparticles by leaf extracts of Cycas circinalis, Ficus amplissima, Commelina benghalensis and Lippia nodiflora

Abstract: Biosynthesis of nanoparticles is a kind of bottom-up approach where the main reaction occurring is reduction. Since silver nanoparticles (AgNPs) have been used for infection prevention in medical field, it is more relevant to reduce their size using ancient Indian herbal plants. This method is good in anti-microbial efficiency against bacteria, viruses and other microorganisms and hence clearly enhances the medicinal usage of AgNPs. This type of green biosynthesis of nanoparticles has received increasing atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…Unfortunately, the XRD pattern was clearly due to the presence of AgCl nanoparticles. Similarly, Johnson and Prabu (2015) reported that Cycas circinalis, Ficus amplissima, Commelina benghalensis, and Lippia nodiflora produced Ag o nanoparticles; however, in the case of F. amplissima, AgCl nanoparticles were clearly produced.…”
Section: Plantsmentioning
confidence: 87%
“…Unfortunately, the XRD pattern was clearly due to the presence of AgCl nanoparticles. Similarly, Johnson and Prabu (2015) reported that Cycas circinalis, Ficus amplissima, Commelina benghalensis, and Lippia nodiflora produced Ag o nanoparticles; however, in the case of F. amplissima, AgCl nanoparticles were clearly produced.…”
Section: Plantsmentioning
confidence: 87%
“…In a related study, Johnson and Prabu observed a rapid reduction capability of Cycas circinalis leaves extracts for Ag ions which led to the formation of crystalline Ag NPs. Similarly, synthesized NPs had spherical shape with diameter of 13-51 nm [95].…”
Section: Gymnospermsmentioning
confidence: 94%
“…The peak at 818 cm -1 is due to C-H bending of alkenes. The peak at 604 cm -1 is due to silver metal vibrations [24]. The adsorption on the surface of silver metal nanoparticles is a characteristic of flavanones and terpenoids [25].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%